Incidence of Impacted Canines in Maxillary Arch - Hanshika Ravi1 , Dinesh Prabu2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The aim of this study is to determine the incidence of impacted canines in maxillary among the patientsvisiting a Dental College.This study was conducted to assess the incidence, frequency, side and associatedsymptoms of impacted canines in maxillary arch.This study was conducted on a hospital based ,matchedcase - control study among the patients visiting saveetha dental college. Data was collected from recordmanagement software.700 case sheets were reviewed from the dental treatment records for presence ofimpacted canines from June 2019-March 2020.Final sample size consist of The above mentioned data wascoded and transferred into a statistical package for social sciences(SPSS) software for statistical analysis.Acorrelation test and chi square analysis was done.The results were recorded.The difference was consideredstatistically significant.Impaction of maxillary canines most commonly occurs in females than in males,mostly buccally placed and most commonly in left arch.